FDM - 3D printing of thermoplastic composites with high energetic solids content designed for gun propellants - Marin Alexandru; Ovidiu George Iorga; Gabriela Toader; Cristiana Epure; Mihail Munteanu; Adrian Nicolae Rotariu; Marius Marmureanu; Gabriel Flavius Noja; Aurel Diacon; Tudor Viorel Tiganescu; Florin Marian Dirloman (Defence Technology, 2025)
This study represents an important step forward in the domain of additive manufacturing of energetic materials. It presents the successful formulation and fabrication by 3D printing of gun propellants using Fused Deposition Modeling (FDM) technology, highlighting the immense potential of this innovative approach. The use of FDM additive manufacturing technology to print gun propellants is a significant advancement due to its novel application in this field, which has not been previously reported. Through this study, the potential of FDM 3D-printing in the production of high-performance energetic composites is demonstrated, and also a new standard for manufacturability in this field can be established. The thermoplastic composites developed in this study are characterized by a notably high energetic solids content, comprising 70% hexogen (RDX) and 10% nitrocellulose (NC), which surpasses the conventional limit of 60% energetic solids typically achieved in stereolithography and light-curing 3D printing methods. The primary objective of the study was to optimize the formulation, enhance performance, and establish an equilibrium between printability and propellant efficacy. Among the three energetic formulations developed for 3D printing feedstock, only two were suitable for printing via the FDM technique. Notably, the formulation consisting of 70% RDX, 10% NC, and 20% polycaprolactone (PCL) emerged as the most advantageous option for gun propellants, owing to its exceptional processability, ease of printability, and high energetic performance.